2015
DOI: 10.1115/1.4031450
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Study on Effects of Drilling Mud Rheological Properties on the Transport of Drilling Cuttings

Abstract: Inaccurate prediction of the required pressures can lead to a number of costly drilling problems. In this study, the hydrodynamics of mud-cuttings were numerically studied using the Mixture Model. To this end, an in-house code was developed to calculate the velocity and pressure fields. The mud velocity profile using of Herschel–Bulkley model and solid phase volume fraction were locally calculated; moreover, pressure drop through the annulus was taken into account. The effects of velocity, mud properties, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…Although experiments have shown that the rolling effect of a small amount of sand can reduce the friction between packers and boreholes, it is very easy to bring an additional local drag due to the accumulation of downhole sand. Therefore, before the completion string enters the horizontal well, the drilling fluid performance needs to be adjusted to meet the requirement of carrying cuttings [38][39][40], and the drilling fluid lubricity should be improved to reduce the friction coefficient between the completion string and the wellbore. In addition, it is necessary to use enhanced operation parameters when pumping on and circulating the drilling fluid at the bottom of the well, such as high flow rate of the drilling fluid and the rotation speed of the drill string [41,42].…”
Section: Decisionsmentioning
confidence: 99%
“…Although experiments have shown that the rolling effect of a small amount of sand can reduce the friction between packers and boreholes, it is very easy to bring an additional local drag due to the accumulation of downhole sand. Therefore, before the completion string enters the horizontal well, the drilling fluid performance needs to be adjusted to meet the requirement of carrying cuttings [38][39][40], and the drilling fluid lubricity should be improved to reduce the friction coefficient between the completion string and the wellbore. In addition, it is necessary to use enhanced operation parameters when pumping on and circulating the drilling fluid at the bottom of the well, such as high flow rate of the drilling fluid and the rotation speed of the drill string [41,42].…”
Section: Decisionsmentioning
confidence: 99%
“…Duan et al (2008) [5] regressed an empirical formula of cuttings bed height based on experimental results. Shadizadeh and Zoveidavianpoor (2012) [6] and GhasemiKafrudi and Hashemabadi (2016) [7] found that a high-viscosity fluid carries cuttings more effectively than a low-viscosity fluid. Yu et al (2007) [8] found that the height of the cuttings bed sharply increases upon a certain drill pipe eccentricity; the torque also increases at this point, resulting in an increased likelihood that the drill will stick.…”
Section: Introductionmentioning
confidence: 99%
“…GhasemiKafrudi and Hashemabadi numerically studied hydrodynamics of drilling fluid (Herschel–Bulkley) with cuttings by the mixture multiphase model. They developed a numerical code to calculate the velocity and pressure profiles in annuli.…”
Section: Introductionmentioning
confidence: 99%